Islamic Psycho-Education for Student Engagement and Academic Stress Reduction: A Quasi-Experimental Study in Indonesian Pesantren - Musslifah, Anniez Rachmawati; Cahyani, Rusnandari Retno; Anwariningsih, Sri Huning; Deporos, Saprolla Rollie C (Universitas Muhammadiyah Yogyakarta, 2025)
Current classroom management in Indonesian pesantren often neglects psycho-spiritual dimensions essential for mitigating academic stress, while empirical evidence on faith-based interventions remains scarce. This quasi-experimental study aimed to evaluate the impact of a structured eight-week Islamic psycho-education intervention on student engagement and academic stress levels. Using a pretest–posttest non-equivalent control group design, participants were 60 pesantren students selected through purposive sampling. The experimental group received an Islamic psycho–education–based classroom management intervention integrated into routine instructional activities, incorporating the muhasabah technique and reflective learning journals grounded in selected Qur’anic verses. Data were collected using the Student Engagement Scale (SES) and the Depression, Anxiety, and Stress Scales (DASS-21). MANCOVA analysis revealed that the intervention significantly increased student engagement (mean difference = +12.4, p < 0.01) and reduced academic stress (−9.7, p < 0.05) compared to controls. Specifically, the integration of tawakal and tazkiyah emerged as a dominant predictor of reduced anxiety (β = −0.42, p = 0.003). This study advances educational and Islamic psychology by empirically supporting the integration of Islamic spiritual constructs into psycho-educational interventions. In practice, the findings support the use of structured Islamic psycho-education in pesantren classroom management and student counseling, offering a culturally responsive model for policy and curriculum development in faith-based education.